Neuropsychiatric symptoms revealing Morgagni-Stewart-Morel syndrome: About 2 cases - Mehdi El Azouzi, MD; Salah Ben El Hend, MD; Amine Bentahar, MD; Abdelghani El Fikri, PhD (Radiology Case Reports)
Internal frontal hyperostosis is a proliferation of the frontal bone that can occur in isolation or in association with neuropsychiatric, metabolic and endocrine symptoms, which together form Morgagni-Stewart-Morel syndrome. In this regard, we report the case of 2 patients meeting the criteria for this syndrome which is revealed by neuropsychiatric manifestations, and a review of the literature is carried out focusing on its pathophysiology.